2017
DOI: 10.1103/physrevlett.119.016403
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Prediction of Spin-Polarized Multiple Dirac Rings in Manganese Fluoride

Abstract: Spin-polarized materials with Dirac features have sparked great scientific interest due to their potential applications in spintronics. But such a type of structure is very rare and none has been fabricated. Here, we investigate the already experimentally synthesized manganese fluoride (MnF 3 ) as a novel spin-polarized Dirac material by using first-principles calculations. MnF 3 exhibits multiple Dirac cones in one spin orientation, while it behaves like a large gap semiconductor in the other spin channel. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 44 publications
0
45
1
Order By: Relevance
“…Interestingly, already prepared MnF 3 had been identified and investigated by chemists for a long time, [83][84][85][86] but there had been no theoretical studies of its electronic band structure. In 2017, Jiao et al 87 demonstrated the DSGS features of MnF 3 by means of first-principles calculations and predicted a series of novel properties. This work focused on a phase of MnF 3 (also called b-MnF 4 ) that had been synthesized in experiments for many years, i.e., its hexagonal bulk structure (space group, R-3c, No.167), corresponding illustration is shown in Fig.…”
Section: Manganese Halidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, already prepared MnF 3 had been identified and investigated by chemists for a long time, [83][84][85][86] but there had been no theoretical studies of its electronic band structure. In 2017, Jiao et al 87 demonstrated the DSGS features of MnF 3 by means of first-principles calculations and predicted a series of novel properties. This work focused on a phase of MnF 3 (also called b-MnF 4 ) that had been synthesized in experiments for many years, i.e., its hexagonal bulk structure (space group, R-3c, No.167), corresponding illustration is shown in Fig.…”
Section: Manganese Halidesmentioning
confidence: 99%
“…We think the following experimental work, which is about achieving true DSGS state by coverage modulation in Mn-intercalated epitaxial graphene on SiC (0001), is still meaningful. Additionally, to achieve further advances in the search for DSGSs that can be synthesized experimentally, we suggest that researchers consider the synthetic potential of compounds such as the 2D graphitic carbon nitrides, 98 TM halides, 80,81,87,90 and simple oxide heterostructures, 69 which are usually built into either honeycomb lattices or cubic types according to computations. The structural designs of these materials are all based on further explorations in well-known traditional compounds (such as tri-s-tri-azine, TMF 3 , and the CrO 2 /TiO 2 heterostructures), which have been widely synthesized and used by chemists for a long time.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Among the intrinsically magnetic 2D materials reported, it is observed that transition‐metal‐centered octahedral unit is one of the key building blocks . The different electronic occupation configurations of transition metal centers and different interaction between transition metals and coordination atoms lead to various exchange processes and magnetic anisotropic strength, and thus various interesting magnetic behaviors observed recently .…”
Section: Introductionmentioning
confidence: 99%
“…The particular nodal rings should be protected by the combination of inversion and time-reversal symmetry, 27 which are expected to have more intensive nonlinear electromagnetic response than Dirac semimetals with a single cone, and thus possess a higher efficiency of carrier trans- port at the Fermi level via multiple Dirac channels. 28 In Imm2-Na 2 B 29 , due to very close structure similarity, the nodal rings could be preserved. However, because of minor concentration of B vacancies, the Fermi level is shifted down by 0.62 eV, to the valence band ( Fig.…”
mentioning
confidence: 97%